Pemantapan program pembangunan di era reformasi - Gunawan Sumodiningrat (Universitas Islam Indonesia, 1999)
Crisis striking Indonesia nowadays is a result of the accumulation of chronic fundamental problems, contagion effect and other complex problems accumulated in the New Order era. Based on the mandate of the People's Consultative Council, government has taken steps to recover the economic condition.